(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the multifaceted role of vowels in language, focusing on how they can be modified across different linguistic contexts. It covers key aspects such as vowel lengthening and shortening, diphthongs, vowel reduction, vowel harmony, and nasalization, providing insights into how these modifications impact pronunciation, meaning, and the overall phonetic structure of a language. The article highlights the dynamic nature of vowels and their importance in distinguishing dialects, accents, and regional speech patterns. Additionally, it emphasizes the centrality of vowel modifications in language evolution, offering a comprehensive understanding of the intricate relationship between sounds and their functions in communication.